2023
DOI: 10.1002/jcla.24966
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Alu methylation in type 2 diabetes mellitus patients increases HbA1c levels

Jirapan Thongsroy,
Apiwat Mutirangura

Abstract: IntroductionAlu hypomethylation is a common epigenetic process that promotes genomic instability with aging phenotypes, which leads to type 2 diabetes mellitus (type 2 DM). Previously, our results showed significantly decreased Alu methylation levels in type 2 DM patients. In this study, we aimed to investigate the longitudinal changes in Alu methylation levels in these patients.ResultsWe observed significantly decreased Alu methylation levels in type 2 DM patients compared with normal (p = 0.0462). Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Also, Alu methylation in patients with T2D progressively decreased with increasing HbA1c levels during a 4-year follow-up period. The authors proposed that this observation suggested a potential link between Alu hypomethylation and the underlying molecular processes, as prolonged hyperglycemia may cause an imbalance in oxidative production and suppression, also induces p53 and may contribute to impaired insulin signaling [43].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, Alu methylation in patients with T2D progressively decreased with increasing HbA1c levels during a 4-year follow-up period. The authors proposed that this observation suggested a potential link between Alu hypomethylation and the underlying molecular processes, as prolonged hyperglycemia may cause an imbalance in oxidative production and suppression, also induces p53 and may contribute to impaired insulin signaling [43].…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory methods: COBRA-interspersed repetitive sequence PCR is a highly accurate semi-quantitative methylation measurement, able to detect more than one CpG site, even when pyrosequencing cannot demonstrate a DNA methylation pattern [15,43]. DNA extraction and bisulfate DNA modification: DNA was extracted from peripheral blood cells using the DNA Blood Mini kit (Qiagen, Hilden, Germany) according to the manufacturer's protocol.…”
Section: Study Design and Participantsmentioning
confidence: 99%
See 1 more Smart Citation